DATA-BASED MARKETING STRATEGIES: IMPACT ON COMPANY PROFITABILITY AND OPERATIONAL EFFICIENCY - Finny Redjeki (Adisam Publisher, 2024)
This research discusses data-based marketing strategies and their impact on company profitability and operational efficiency. The main focus is how the application of customer data analysis can provide deeper insight into consumer needs and preferences. This allows companies to craft more personalized and relevant marketing campaigns, which in turn can increase customer retention rates and sales conversion opportunities. Findings show that data-driven marketing strategies contribute significantly to increased profitability and operational efficiency. Using the right data allows companies to allocate marketing resources more effectively, reduce waste, and increase ROI (Return on Investment). However, the challenges of managing and integrating data from multiple sources, as well as complying with privacy regulations, remain obstacles that must be overcome. The results of this research confirm that investment in technology, development of human resource analytical capacity, and implementation of an organizational culture that supports data-based decision making are key success factors. With the right strategy, companies can gain competitive advantage, increase profitability, and achieve optimal operational efficiency.